2019
DOI: 10.20961/prosidingsnfa.v3i0.28516
|View full text |Cite
|
Sign up to set email alerts
|

Terhadap Kemampuan Berpikir Kritis Pada Mata Pelajaran Ipa

Abstract: <p class="AbstractEnglish"><strong>Abstract: </strong>This research applies a guided inquiry method that is used to improve critical thinking skills in cognitive categories, general and special affective disposition categories and to determine the difference in the proportion of scores of six critical thinking elements in the cognitive category of fifth-grade students in four Kanisius elementary schools in Yogyakarta. The type of research used quantitative research. Critical thinking ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Putra et al (2019) research results indicate that teachers still need to be more optimal in training students to think critically and analyze and evaluate problems in learning biology. The low fact about empowering students' critical thinking is also revealed in the research of Budi & Ghofar (2017), Falah et al (2018), Kurniawati et al (2015), Nuraini (2017), andSudin et al (2018).…”
Section: A Introductionmentioning
confidence: 87%
“…Putra et al (2019) research results indicate that teachers still need to be more optimal in training students to think critically and analyze and evaluate problems in learning biology. The low fact about empowering students' critical thinking is also revealed in the research of Budi & Ghofar (2017), Falah et al (2018), Kurniawati et al (2015), Nuraini (2017), andSudin et al (2018).…”
Section: A Introductionmentioning
confidence: 87%
“…Kegiatan mengeksplanasi dalam LKPD disajikan dalam bentuk eksplanasi hasil praktikum uji urine. Dengan kegiatan eksplanasi, peserta didik dilatih untuk dapat menyajikan informasi dari hasil pemikiran dengan cara yang meyakinkan dan koheren (Rositawati, 2018). Kegiatan eksplanasi dapat mengarahkan peserta didik untuk mempertimbangkan terlebih dahulu argumen yang akan disampaikan dengan berdasar pada konsep, bukti, metodologi, dan kriteria yang logis sesuai dengan informasi yang ada (Facione, 2015).…”
Section: Aspek Yang Dinilai Skorunclassified
“…Although research conducted in an Indonesian learning context revealed students' deficiency in mastering the skills, critical thinking skills play a significant influence in students' performance in learning (Halpern, et al, 2012). Critical thinking skills play a major role in students' success in learning (Halpern, et al, 2012); however, research conducted within an Indonesian learning context showed students' insufficiency in mastering the skills, especially critical thinking skills (Kurniawati et al, 2015). Also, because of the implementation of incompatible and discouraging learning models, facts also prove that critical thinking skills of high school students in Malang, especially in Biology, fall into the low category (Corebima, 2016).…”
Section: Introductionmentioning
confidence: 96%